Muslims in Contemporary Australia - Possamai, Adam,; Tittensor, David, (Middle East and Islamic Studies E-Books Online, Collection 2025., 2025)
This edited book provides a much-needed update on the field of Islamic Studies in Australia, which has come a long way since the pioneering work of both Riaz Hassan and Gary Bouma to whom this volume is indebted. By highlighting the richness of the contributions of Muslim Australians in diverse areas such as art, literature, architecture and popular culture, alongside the more standard sociological contributions on the ongoing challenges, this book will inspire researchers to look beyond the hackneyed notions of conflict, difference and fear, and seek to tell stories that glimpse behind the curtain and give insight into the Australian Muslim 'backstage' experience.